Money Dwells in the Spiritual Pocket! The Gospel of Prosperity and the Empowerment of Women through Talents/Matarenda among ZAOGA FIF Adherents in Gweru, Zimbabwe - Annah Moyo; Gilbert Tarugarira (Journal for the Study of Religion)
Some religious movements have instilled a creative and innovative spirit among their adherents. This spirit is coupled with hard work and the inculcation of skills towards making a better life for themselves and their families. Referring to the Zimbabwe Assemblies of God Africa – Forward in Faith (ZAOGA FIF), this essay explores how this church organization has instilled hard work, frugality, and penultimate economic empowerment among its followers through Talents/Matarenda. The essay has employed the Empowerment Framework of Longwe and Clarke (1994) as an analytical tool to unpack the church’s approach towards the empowerment of women. It has established positive changes in people’s quality of life amidst conflicts and compromises between the maintenance of religious ethical standards and the primacy of the economic motives in the adherents’ quest for material wealth.